2007
DOI: 10.1007/s11340-007-9072-6
|View full text |Cite
|
Sign up to set email alerts
|

Stiffening and Contraction Induced by Dexamethasone in Alveolar Epithelial Cells

Abstract: Background The structural integrity of the alveolar monolayer, which is compromised during lung inflammation, is determined by the balance between cell-cell and cell-matrix tethering forces and the centripetal forces owing to cell viscoelasticity and contraction. Dexamethasone is an anti-inflammatory glucocorticoid with protective effects in lung injury. Aim To determine the effects of Dexamethasone on the stiffness and contractility of alveolar epithelial cells. Methods Cell stiffness (G′) and average tractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 42 publications
2
12
0
Order By: Relevance
“…Based on these findings and the fact that A549 cells can also express different proteins involved in the coagulation cascade [5], [22], [23] and can generate new APC in the presence of thrombin and protein C antigen [24], we considered the A549 cell line an appropriate model to study the effects of APC on the structural integrity of the alveolar epithelial monolayer subjected to thrombin. Moreover, the acute thrombin response found in A549 cell permeability is in line with several data showing that thrombin induces a more marked effect after five minutes of treatment [8], [10], [14], [18]. In agreement with previous studies, we found that thrombin stiffens and contracts alveolar epithelial cells, suggesting an increase in inward forces compromising the barrier integrity [8], [9], [18].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Based on these findings and the fact that A549 cells can also express different proteins involved in the coagulation cascade [5], [22], [23] and can generate new APC in the presence of thrombin and protein C antigen [24], we considered the A549 cell line an appropriate model to study the effects of APC on the structural integrity of the alveolar epithelial monolayer subjected to thrombin. Moreover, the acute thrombin response found in A549 cell permeability is in line with several data showing that thrombin induces a more marked effect after five minutes of treatment [8], [10], [14], [18]. In agreement with previous studies, we found that thrombin stiffens and contracts alveolar epithelial cells, suggesting an increase in inward forces compromising the barrier integrity [8], [9], [18].…”
Section: Discussionsupporting
confidence: 93%
“…In this simple model, paracellular gaps form and the barrier is disrupted when adhesive cell-cell and cell-matrix tethering forces that regulate cell shape are unable to withstand cell tension forces exerted by cytoskeleton viscoelastic recoil and contraction of the actomyosin machinery [3]. In particular, thrombin can modulate this force balance [8][10], [18], acting near the site of its generation [19] through protease-activated receptors (PAR-1, PAR-3, and PAR-4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Salsas-Escat et al [45] employed molecular simulations to illustrate the structural conformations of collagen and the inherent flexibility of certain regions of the molecular structure. In a cellular pharmacology study, Puig et al [46] demonstrated that the application of dexamethasone, an anti-inflammatory glucocorticoid that affects actin cytoskeleton remodelling, led to an increase in alveolar epithelial cell stiffness and average traction force as measured by magnetic twisting cytometry. Yuan et al [47] reported on a novel method to quantify the torque generated by the E. coli flagellar motor, powered by various cytoskeletal elements, near zero load.…”
Section: Cellular and Subcellular Biomechanicsmentioning
confidence: 99%